Coaching Nenek ASI Sebagai Upaya Meningkatkan Pengetahuan Nenek tentang Asi Eksklusif di Kota Pekanbaru - Hetty Ismainar; Hayana Hayana; Hastuti Marlina (STIKes Hang Tuah Pekanbaru, 2021)
Background. Basic Health Research data on the achievement of exclusive breastfeeding programs in Indonesia in 2018 was only 38% (the government's target of >80%). One of the efforts to increase the coverage of exclusive breastfeeding is the support of the closest family, especially grandmothers. The Objective of the activity is to provide grandmothers coaching to increase knowledge and understanding of exclusive breastfeeding. The breastfeeding grandmother’s coaching Method used lectures and online media demonstrations using the Google Meet application. The coaching media included running videos about exclusive breastfeeding, leaflets, and brochures. Participants were grandmothers who have grandchildren living with them. The total participants were 55 grandmothers who live in the Gading Marpoyan Housing Pekanbaru. Measurement of participants' understanding was seen by giving pre-test and post-test about exclusive breastfeeding. All respondents filled out the google form given before and after the activity. The coaching materials were health education information about the explanation of exclusive breastfeeding, the benefits of exclusive breastfeeding for mothers and families, myths and fact about exclusive breastfeeding, and the role of grandmothers in exclusive breastfeeding. The result of the pre-test showed that the average knowledge was low (42.54%), moderate (37.46%), and high (19.98%). There was a significant increase in the post-test scores by 63,3%. Knowledge was low (6.54%), medium (10.16%), and high (83.28%). Conclusions. The breastfeeding grandmother coaching program is considered effective in increasing the knowledge and role of grandmothers in exclusive breastfeeding. ABSTRAK Latar Belakang Data Riset Kesehatan Dasar tentang capaian program ASI Eksklusif di Indonesia tahun 2018 hanya 38% (target capaian pemerintah >80%). Salah satu upaya untuk meningkatkan cakupan ASI eksklusif adalah dukungan keluarga terdekat terutama nenek. Tujuan kegiatan untuk memberikan coaching (pelatihan) pada nenek untuk meningkatkan pengetahuan dan pemahaman tentang ASI Eksklusif. Metode coaching nenek asi menggunakan ceramah dan demonstrasi media online aplikasi google meet. Media pelatihan berupa pemutaran video tentang ASI ekslusif, leaflet dan brosur. Peserta adalah nenek yang memiliki cucu yang tinggal bersamanya. Total peserta 55 orang nenek yang berdomisili di komplek perumahan Gading Marpoyan Kota Pekanbaru. Pengukuran pemahaman peserta dilihat dengan memberikan pre- test dan post-test tentang ASI Eksklusif. Seluruh responden mengisi google form yang diberikan sebelum dan sesudah kegiatan. Materi coaching adalah informasi edukasi kesehatan tentang definisi ASI ekslusif, manfaat ASI ekslusif bagi ibu dan keluarga, mitos dan fakta tentang ASI ekslusif dan peran nenek dalam pemberian ASI eksklusif. Hasil nilai pre-test menunjukkan rata-rata pengetahuan rendah (42.54%), sedang (37.46%) dan tinggi (19.98%). Nilai post-test terjadi peningkatan yang siginifikan yaitu 63,3%. Pengetahuan rendah (6.54%), sedang (10,16%) dan tinggi (83.28%). Kesimpulan Program coaching nenek ASI ini dinilai efektif meningkatkan pengetahuan dan peran nenek dalam ASI eksklusif.